KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK AISYIYAH SE-KOTA PONTIANAK - Lulu Fitriani; Elin; Diana (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
The research aims to determine the fine-motoric skills of children aged 5-6 years in tearing, cutting, and folding paper. This study uses a quantitative approach. The form of research used is observation (survey), by observing fine motor activities in children aged 5-6 years. Data collection tools used in this research are instruments, interview guides, and documentation. Data processing techniques use percentage calculations, and the calculation results will enter into the categories provided in this study. In the fine motor skills of Aisyiyah Kindergarten children in Pontianak City, the ability to tear, cut and fold paper classification is in the superb category